Quantifying the local tissue volume and composition in individual brains with magnetic resonance imaging - Mezer, Aviv; Yeatman, Jason D; Stikov, Nikola; Kay, Kendrick N; Cho, Nam-Joon; Dougherty, Robert F; Perry, Michael L; Parvizi, Josef; Hua, Le H; Butts-Pauly, Kim; Wandell, Brian A (Nature medicine, 2013)
There is an urgent need for quantitative magnetic resonance approaches for assessing brain development, as well as for studying the effects of drugs on neural tissue inflammation. Aviv Mezer and colleagues have developed a neuroimaging method for the quantification of local tissue volume and tissue-surface interaction, producing reliable quantitative measurements across a range of scanners. They apply their method to both the healthy brain and individuals with relapsing-remitting multiple sclerosis. Here, we describe a quantitative neuroimaging method to estimate the macromolecular tissue volume (MTV), a fundamental measure of brain anatomy. By making measurements over a range of field strengths and scan parameters, we tested the key assumptions and the robustness of the method. The measurements confirm that a consistent quantitative estimate of MTV can be obtained across a range of scanners. MTV estimates are sufficiently precise to enable a comparison between data obtained from an individual subject with control population data. We describe two applications. First, we show that MTV estimates can be combined with T1 and diffusion measurements to augment our understanding of the tissue properties. Second, we show that MTV provides a sensitive measure of disease status in individual patients with multiple sclerosis. The MTV maps are obtained using short clinically appropriate scans that can reveal how tissue changes influence behavior and cognition.